Boundary of Istimta' For Husband Against Menstruating Wife (Comparative Study of Imam Malik and Imam As Syafi'i) - Hakim, Pahmi; Efendi, Rahmad (Fakultas Syariah INSURI Ponorogo, 2023)
This research examines the